Efficient Adsorption of Chromium(VI) Ions from Aqueous Solution onto a Low-Cost Adsorbent Developed from (Wood Apple) Shell - Ashish S. Sartape; Prakash D. Raut; Sanjay S. Kolekar (Adsorption Science & Technology)
The removal of chromium(VI) ions from aqueous solution was studied using Limonia acidissima (wood apple) shell activated carbon. The removal extent was found to be a maximum at a pH value of 2, with the lowcost adsorbent having an adsorption capacity of 13.74 mg/g. The material employed was characterized by scanning electron microscopy (SEM), Fouriertransform infrared spectroscopy (FT-IR) and elemental analysis. The linear Freundlich and Langmuir adsorption isotherm models were applied to describe the experimental equilibrium isotherms. The results showed that the Langmuir equation gave a better fit to the experimental data than the Freundlich equation. The pseudo-first-order and pseudo-second-order models were applied to the adsorption kinetics of Cr(VI) ions onto wood apple shell activated carbon. Thermodynamic parameters such as the standard enthalpy (ΔH 0 ), the Gibbs' free energy (ΔG 0 ) and the standard entropy (ΔS 0 ) were evaluated and indicated that the sorption process was spontaneous and endothermic in nature. The results demonstrated that wood apple shell activated carbon may be effectively used for the inexpensive removal of Cr(VI) ions from aqueous solution.